Sharia tribunals, Rabbinical courts, and Christian panels : religious arbitration in America and the West - Broyde, Michael J. (New York, NY : Oxford University Press, 2017)
This text explores the rise of private arbitration in religious and other values-oriented communities, and it argues that secular societies should use secular legal frameworks to facilitate, enforce, and regulate religious arbitration, including those from Rabbinical Courts, Sharia Tribunals, and any faith-based arbitration tribunals.
Previously issued in print: 2017.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 9, 2017).
Keywords: Ecclesiastical courts -- United States; Dispute resolution (Law) -- United States; Church and state -- United States; Islamic courts -- United States; Rabbinical courts -- United States; Law; Laws of specific jurisdictions & specific areas of law